Performance assessment of wind farms - Vaz, Clara B. (2014)
This study develops a methodology to provide insights regarding the performance of the wind farms of a European player in the energy sector. The focus of the wind farm performance assessment is on the operating stage which corresponds to the electrical energy generation process. Firstly, the Data Envelopment Analysis is used to measure the performance of wind farms in generating electrical energy from the resources available and exogenous variables, during the period under analysis. This analysis enables the identification of the best practices of the efficient farms which can be emulated by inefficient ones. Secondly, bootstrap procedures are applied to obtain statistical inference on the efficiency estimates. The performance assessment approach proposed will be useful for promoters in the management and control of wind farms and for the installation of wind farms in new areas, but also for repowering processes in existing farms.